Legitimizing videogames as art: John Dewey's philosophy of art and the nature of videogames - Esteban, Aaron Micah A. (Animo Repository, 2023)
Roger Ebert (2010), a distinguished film critic, maintains that videogames are by nature “the opposite of the strategy of serious film and literature, which requires authorial control.” Ebert’s claim that videogames cannot be art stimulated serious philosophical discussions on the aesthetics of videogames. Aaron Smuts (2005) in Are Video Games Art? disputed that existing aesthetic theories such as historical, representational and institutional theories can consider videogames as art. Grant Tavinor (2009) continued the discussion in his book The Art of Videogames by proposing the method of cluster theory as a preferred aesthetic theory. Consequently, Phillip Deen (2011) framed the debate towards the interactive nature of videogames. He claims that experiential aesthetics such as John Dewey’s aesthetic theory can properly advance the unique qualities of videogames. These games involve the audience’s active participation as opposed to Ebert’s claim of being a passive spectator. The philosophers presented theories on what constitutes a videogame and how it can be art by using numerous game titles as examples. Although I agree with Philip Deen’s claim, his study is insufficient. In line with this, the primary aim of my dissertation is to argue that videogames can be art through John Dewey’s experiential aesthetic theory. After evaluating the nature of videogames through Dewey’s philosophy of art, I will then assess two videogames, God of War (Santa Monica Studio 2018) and Hellblade: Senua’s Sacrifice (Ninja Theory 2017), to demonstrate Dewey’s experiential aesthetic theory. Keywords: Videogames, Experiential Aesthetic Theory, Dewey, Interactivity, Art